Предмет: Алгебра,
автор: Maaks123
17-2 (x+3) +5 (x-7) -3 (2x+1) = -28 помогите решить желательно вместе с решением! спасибо
Ответы
Автор ответа:
0
17-2 (x+3) +5 (x-7) -3 (2x+1) = -28
17-2х-6+5х-35-6х-3=-28
-2х+5х-6х=-28+27
-3х=-1
Х=1/3
17-2х-6+5х-35-6х-3=-28
-2х+5х-6х=-28+27
-3х=-1
Х=1/3
Похожие вопросы
Предмет: Литература,
автор: aisulu1771
Предмет: Литература,
автор: gavrilukangelina634
Предмет: Математика,
автор: fr0nyyyy
Предмет: Математика,
автор: vladoslav19092002
Предмет: Математика,
автор: polina271203